An Analysis of Mergers and Acquisition in Iron and Steel Sector - Bagaria, Sonal (2009)
Although mergers and acquisitions have been an essential element of corporate strategy all over the world for several years, but it still remains a puzzle if there are substantial gains from mergers in the long run. There is thus a constant debate on the consequence of M&A’s on firms. However, few appear to be aware about the long term post performance of firms and the strategic factors that affect this performance. My research puts an effort to provide brief knowledge about performance of companies in light of their merger and acquisition activities. I have used sample size of 51 companies covering UK, Luxemburg and USA from the iron and steel sector and examined the change in companies’ share prices after undergoing a merger or acquisition. This research studies the performance of mergers and acquisitions and its influence on the returns to the shareholders of the acquiring firm surrounding the announcement days. The event study with market model approach is used to calculate the profitability of a merger and then consider different statistical test results to examine that. To understand the variations in the returns to shareholder’s on account on a merger/acquisition activity the research is linked to some factor which might be closely related to returns to the bidder shareholders on the days surrounding the announcement. The research focuses on different deal size as a crucial parameter for impacting the returns.